Gender And Body: Youth Discussion About Self-Identity Construction on Interpersonal Communication - Annisa Anindya; Novi Elian; Sarmiati Sarmiati (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2022)
Youths are facing unprecedented change and uncertainty, such as gender equality, mental health, industry, and the corporation of the adult world. The rise of the issue of gender equality in Indonesia is accompanied by changes in construction society in the depiction of gender. This research is using multi-method qualitative approach, focus on exploring the narratives of youths as they fixed their self-identity with in-depth interview. The theory that is using in this study is Anthony Gidddens' theory: modernity, and self-identity. It portrays the condition of young people who are attached to society's constructs about interpreting gender. Gender and body are not only talk about men or women but show in performance and controlled by society. This research found that showing the masculine and feminine side did not change the self-identity of the subjects.